STRATEGI PUBLIC RELATIONS â€œBINA ANTARBUDAYAâ€ DALAM MENARIK MINAT SISWA SMA SEDERAJAT UNTUK MENGIKUTI INTERCULTURAL PROGRAM (Studi Kualitatif Deskriptif di Bina Antarbudaya chapter Surabaya) - Ainurrahmah, Salma; Sumarah, Noorshanti; Danadartha, Irmasanthi (Universitas 17 Agustus 1945 Surabaya, 2018)
Intercultural communication is an unavoidable thing in the globalization era. Based on this fact, Non Government Organization Bina Antarbudaya chapter Surabaya has a specific purpose to deliver intercultural learning through intercultural programs. However, to attract the target public, which is high school students has several obstacles. This research discusses about Public Relations Strategy of Bina Antarbudaya chapter Surabaya, by using Public Relations Mix theory as a tool of analyzing the data. Moreover, this research is using qualitative method and descriptive approach. Data collection is done by conducting interviews and observing the system of Public Relations strategy in Bina Antarbudaya chapter Surabaya.It was found a new fact during the research, Bina Antarbudaya chapter Surabaya has changed several things in their Public Relations strategy, due to the expansion of public targets. The new strategy is to make a Roadshows program to schools outside Surabaya that has no information about Bina Antarbudaya chapter Surabaya yet. Besides the Roadshow progam, as the first goal of Bina Antarbudaya chapter Surabaya also still doing publications that very dependent on the power of social media, especially Instagram, Direct Approach also still implemented by carry out routine activities as one of a way to show organizational existence and to reach their target for high school students' interest in participating in the Intercultural Program.Keywords: intercultural program, non government organization, public relations